Disease Recurrence and Acute Cellular Rejection Episodes During the First Year After Lung Transplantation Among Patients With Sarcoidosis. Issue 9 (September 2015) - Banga, Amit; Sahoo, Debasis; Lane, Charles R.; Farver, Carol F.; Budev, Marie M.
Abstract : Introduction: Sarcoidosis is reported to recur after lung transplantation (LT). We sought to determine the frequency of recurrent disease after LT and predictors of recurrence. We also evaluated the incidence and severity of acute cellular rejection (ACR) episodes among these patients. Methods: The database of LT patients at Cleveland Clinic was interrogated for sarcoidosis patients who underwent LT between May 1993 and 2011. Charts were reviewed for demographics, type of transplant, posttransplant biopsy findings, and outcomes. Results: Data were available for 30 patients (mean age, 50 ± 9.3 years; range, 30-65 years; M-to-F ratio, 17:13; single-to-double-to-heart lung ratio, 5:24:1). Recurrence of sarcoidosis was noted among 7 patients (pathological recurrence in all and radiological findings suggesting recurrence in 1 patient) with no impact on overall outcomes. Presence of granulomas on explanted lungs was the only predictor of recurrence (85.7% vs 30.4%, odds ratio, 13.7; 1.4-136.2; P = 0.02). Overall burden of ACR episodes on all bronchoscopies was significantly lower in patients with disease recurrence (7.6 % vs 21.3% of biopsies, P = 0.038). Among patients with recurrent disease, ACR did not develop once disease recurrence had been seen on transbronchial biopsy. Conclusions: A significant proportion of sarcoidosis patients have disease recurrence after LT and presence of active granulomas on explant is associated with subsequent recurrence. There may be an association of recurrence with lower frequency of ACR episodes. There does not appear to be any impact of sarcoidosis recurrence on 1-, 3-, or 5-year survivals. Abstract : This single-center, retrospective analysis of lung allograft recipients transplanted for sarcoidosis shows almost 25% recurrence of sarcoid, but without a negative consequence for allograft survival. Recipients with recurrence have lower rates of acute cellular rejection.